Pengaruh Pengekstrakan pada Kekuatan Kayu: Damar Batu, Kempas, dan Durian - Iskandar Iskandar (Jurnal Rekayasa Kimia & Lingkungan)
The objective of this research is to determine strength rate of Damar Batu/Balau (Shorea spp.), Kempas (Kompassia malaccensis), and Durian (Durio spp.) before and after extraction. For this purpose, three solvents were used in sequence to extract the wood which are acetone pentane, and mixture of hexane, acetone, and water (HAW) with volume ratio 55:44:2. Studies on the wood comprises of tensile, bending, and impact test. The tests are conducted based on method of ASTM D 3500 – 90, ASTM D 3043 – 95, and ASTM D 1e43 – 94 for tensile, bending, and impact test, respectively. The result showed that Damar Batu/Balau has higher strength compared to Kempas and Durian Woods. All the wood samples after extraction show a slight decreasing in tensile strength, tensile extension, and flexural stress, whereby modulus tensile, modulus flexural, and impact strength increases.